2002
DOI: 10.1038/sj.jhh.1001416
|View full text |Cite
|
Sign up to set email alerts
|

Mecamylamine (Inversine®): an old antihypertensive with new research directions

Abstract: Mecamylamine (Inversine  ), the first orally available antihypertensive agent, is now rarely used. Although celebrated in the 1950s, mecamylamine fell out of favour because of its widespread ganglionic side effects at antihypertensive doses (30-90 mg/day). However, recent studies suggest that mecamylamine is very effective at relatively low doses (2.5-5 mg b.i.d.) for blocking the physiological effects of nicotine and improving abstinence rates in smoking cessation studies, particularly for women. When these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 33 publications
1
60
0
Order By: Relevance
“…Schuller et al have also shown that the nitrosamine 4-(methylnitrosamino)-I-(3-pyridyl)-1-butanone (NNK) that is present in tobacco smoke similarly stimulates lung cancer growth through nicotinic receptors and MAPK-dependent mechanisms (23,26). Although treatment with nicotinic receptor antagonists can have significant effects on blood pressure (27), muscarinic receptor antagonists are better tolerated and are widely used for treatment of chronic obstructive pulmonary disease (COPD; ref. 28) and overactive bladder (29).…”
Section: Introductionmentioning
confidence: 99%
“…Schuller et al have also shown that the nitrosamine 4-(methylnitrosamino)-I-(3-pyridyl)-1-butanone (NNK) that is present in tobacco smoke similarly stimulates lung cancer growth through nicotinic receptors and MAPK-dependent mechanisms (23,26). Although treatment with nicotinic receptor antagonists can have significant effects on blood pressure (27), muscarinic receptor antagonists are better tolerated and are widely used for treatment of chronic obstructive pulmonary disease (COPD; ref. 28) and overactive bladder (29).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that in some respects, nicotine exerts a longer-term effect similar to an antagonist. Mecamylamine has a range of action across different doses, including cognitive enhancement (Mihailescu et al 1998;Giniatullin et al 2000;Buccafusco and Terry, 2002;Shytle et al 2002). …”
mentioning
confidence: 99%
“…Previous work has also suggested the participation of nicotinic acetylcholine receptors (nAChR) (22,23) in the detection of nicotine by the peripheral taste system. The role of nAChRs in taste responses to nicotine is particularly intriguing because mecamylamine, a broad spectrum nAChR antagonist that has been used as a smoking cessation aid (24), reduces the sensitivity to peripheral sensory stimulation by cigarette smoke (25). However, hexamethonium (22), a different nAChR antagonist, inhibits taste responses to nicotine as well as to other tastants, suggesting that the inhibition resulting from nAChR antagonism may be unspecific.…”
mentioning
confidence: 99%